Treatment intensity significantly influencing fibrosis in bone marrow independently of the cytogenetic response: meta-analysis of the long-term results from two prospective controlled trials on chronic myeloid leukemia - Büsche, Guntram; Freund, M.; Hehlmann, Rüdiger; Georgii, A.; Ganser, A.; Hecker, H.; Heimpel, H.; Fonatsch, C.; Heinze, B.; Pfirrmann, M.; Holgado, S.; Schmeil, A.; et al. (Leukemia, 2004)
Bone marrow fibrosis (MF) has been shown to indicate therapy failure in Ph+ chronic myeloid leukemia (CML). However, the results on the development of MF during interferon-α therapy of CML are controversial. The significance of the interferon dose has not been considered as yet. In total, 627 bone marrow biopsies taken prospectively from 200 patients with CML recruited in two studies using different doses of interferon-α ± low-dose cytosine arabinoside were examined for MF before and during therapy. The results showed that the risk of MF depended significantly on the interferon-α dose applied (P<0.000005). MF progressed during low-dose therapy (3 × 5 × 106 IU/week), but was prevented from progression when applying high dose (5 × 106 IU/m2/per day). MF disappeared when high-dose interferon-α was combined with low-dose cytosine arabinoside (P<0.000005). The risk of death markedly increased when MF occurred or progressed (P<0.0009), independent of all other prognostic factors evaluated including the cytogenetic response. In conclusion, the effectiveness of interferon-α on MF depends on the treatment intensity. MF reverses when combining high-dose interferon-α with low-dose cytosine arabinoside, but progresses when applying low-dose interferon-α. MF appears to be a significant early indicator of ineffective therapy in CML.
Gesehen am 13.05.2022